2008
DOI: 10.1007/s10570-008-9270-0
|View full text |Cite
|
Sign up to set email alerts
|

Rendering cellulose fibers antimicrobial using cationic β-cyclodextrin-based polymers included with antibiotics

Abstract: Cationic b-cyclodextrin polymer (CPbCD) and its complexes with butylparaben and triclosan were reported in this paper. 2D NMR confirmed that the host-guest complexes were formed by including antibiotics inside the cavities of CPbCDs, which significantly improved the water solubility of the antibiotics. Results of inhibition zones and shaking flask methods of antimicrobialmodified cellulose fibres showed that both antibiotics/ CPbCD complexes had excellent antimicrobial activities when applying on the cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Recent examples are cationic polymer modified silica nanoparticles with enhanced antibacterial performance compared to bulk polycations and reduced adhesion on the surface of glass [267], non-leaching antimicrobial polyamide nanocomposites based on organoclays modified with a cationic polymer [268], cationic β-cyclodextrin-based polymers complexed with antibiotics such as butylparaben and triclosan and used to adsorb onto cellulose fibers; these affected the metabolism of the bacteria instead of damaging the cell membrane [269], antimicrobial and cationic polyhexamethylene guanidine hydrochloride (CPHGH) assembled to temperature-responsive, acetalyzed poly(vinyl alc. )/sodium acrylate (APVA-co-AANa) as multilayers [270], copolymers of 4-vinyl- N -hexylpyridinium bromide and dimethyl(2-methacryloyloxyethyl) phosphonate self-assembled onto titanium surfaces to form biocompatible and antimicrobial ultrathin layers able to prevent biofilm formation on implants [271], chitosan formulations, complexes and derivatives with other substances able to prevent or treat wound and burn infections not only because of its intrinsic antimicrobial properties, but also by virtue of its ability to deliver extrinsic antimicrobial agents to wounds and burns [200], hydrogels, formed by cationic polymers alone, or polymer mixtures with antimicrobial surfactants, lipids, nanoparticles, peptides, antibiotics or antiviral drugs [272], metallic-based micro and nano-structured materials such as copper, zinc and titanium and their oxides assembled into polymers with the migration of cations from the polymer matrixes determining their antimicrobial effectiveness [273275], nonwoven poly(ethylene terephthalate) assembled with cationic quaternary ammonium antimicrobial polymer [276], rayon fibres made antimicrobial and thermal-responsive via layer-by-layer assembly with the appropriate functional polymers [277], silver nanoparticles capped with diaminopyridinylated heparin (DAPHP) and hyaluronan (HA) polysaccharides [278], etc.…”
Section: The Antimicrobial Supramolecular Assembliesmentioning
confidence: 99%
“…Recent examples are cationic polymer modified silica nanoparticles with enhanced antibacterial performance compared to bulk polycations and reduced adhesion on the surface of glass [267], non-leaching antimicrobial polyamide nanocomposites based on organoclays modified with a cationic polymer [268], cationic β-cyclodextrin-based polymers complexed with antibiotics such as butylparaben and triclosan and used to adsorb onto cellulose fibers; these affected the metabolism of the bacteria instead of damaging the cell membrane [269], antimicrobial and cationic polyhexamethylene guanidine hydrochloride (CPHGH) assembled to temperature-responsive, acetalyzed poly(vinyl alc. )/sodium acrylate (APVA-co-AANa) as multilayers [270], copolymers of 4-vinyl- N -hexylpyridinium bromide and dimethyl(2-methacryloyloxyethyl) phosphonate self-assembled onto titanium surfaces to form biocompatible and antimicrobial ultrathin layers able to prevent biofilm formation on implants [271], chitosan formulations, complexes and derivatives with other substances able to prevent or treat wound and burn infections not only because of its intrinsic antimicrobial properties, but also by virtue of its ability to deliver extrinsic antimicrobial agents to wounds and burns [200], hydrogels, formed by cationic polymers alone, or polymer mixtures with antimicrobial surfactants, lipids, nanoparticles, peptides, antibiotics or antiviral drugs [272], metallic-based micro and nano-structured materials such as copper, zinc and titanium and their oxides assembled into polymers with the migration of cations from the polymer matrixes determining their antimicrobial effectiveness [273275], nonwoven poly(ethylene terephthalate) assembled with cationic quaternary ammonium antimicrobial polymer [276], rayon fibres made antimicrobial and thermal-responsive via layer-by-layer assembly with the appropriate functional polymers [277], silver nanoparticles capped with diaminopyridinylated heparin (DAPHP) and hyaluronan (HA) polysaccharides [278], etc.…”
Section: The Antimicrobial Supramolecular Assembliesmentioning
confidence: 99%
“…The antimicrobial properties of such materials can be evaluated by measuring the diameter of the inhibition zones. 25,26 With regard to antimicrobial materials without the leaching effect, although they held the same ability to deactivate bacteria, there will not be any inhibition zone around the test sample. From the results in Figure 2, none of the films prepared in this work have shown any inhibition zone, which confirmed the nonleaching effect.…”
Section: Resultsmentioning
confidence: 99%
“…The typical scheme of synthesising cationic b-CD-based polymer and forming a host-guest complex with antibiotics is shown in Scheme 4.5. 37 During the reaction, EP plays an important role as crosslinker for imparting cationic charge to b-CD and polymerising to cationic polymer. Five b-CD molecules were contained in one cationic polymer averagely according to the molecular weight of cationic polymer measured by gel permeation chromatography (GPC).…”
Section: Cyclodextrin-based Polymer/antibiotics (Cpbcd) Complex As Fumentioning
confidence: 99%
“…It was found that the inhibition effect of the spraying is better than that of the adsorption (see the results in Table 4.2). 37 The shaking flask method is also an effective way to assess the antimicrobial activity of paper products. The effects of antibiotic concentration and contacting time are listed in Table 4.3.…”
Section: Cyclodextrin-based Polymer/antibiotics (Cpbcd) Complex As Fumentioning
confidence: 99%